The perceived fairness of layoffs in Germany: Participation, compensation, or avoidance ? - Pfeifer, Christian (2007)
This study analyses to what extend and under what circumstances layoffs are accepted in Germany. Principles of distributive justice and rules of procedural justice form the theoretical framework of the analysis. Based on this, hypotheses are generated, which are tested empirically in a telephone survey conducted between East and West Germans in 2004 (n = 3036). The empirical analysis accounts for the different points of views of implicated stakeholders and impartial spectators. Key findings are: (1) The management of a company can increase the acceptance of layoffs if the employees get some participation rights. (2) For impartial spectators generous compensation for those made redundant leads to a higher degree of perceived fairness. But job alliances are not even preferred to layoffs without measures to soften the blow of job loss. (3) Implicated stakeholders accept job alliances and perceive wage cuts as more fair than layoffs. However, compensation does not have the expected impact.